Chemical and Physical Sputtering of Polyethylene Terephthalate (PET). Issue 3 (21st December 2012) - Große‐Kreul, Simon; Corbella, Carles; von Keudell, Achim
Abstract The polymer polyethylene terephthalate (PET) has been exposed to quantified beams of argon ions and oxygen atoms and molecules. The etch rate (ER) and the surface composition of PET thin films have been analyzed by real time in situ Fourier transform infrared spectroscopy (FTIR). After the onset of the exposure of PET to the ion beam, the ER decreases rapidly by one order of magnitude irrespective of the ion energy. This slowing down of the ER is caused by cross‐linking of the polymer surface. The steady state etch yields are generally orders of magnitude higher than predicted by computer calculations. The addition of oxygen to the particle flux is only changing the surface composition. At low ion energies, chemical sputtering dominates causing very high sputter yields. In addition, no threshold ion energy is observed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>